Menjaga Integritas Aparatur Hukum: Etika Profesi dalam Pelayanan Publik - Vindy Karina Leksono; Tsabita Az Zahra; Rahma Dhani Dian Wijayanti; Berliana Clara Bella; Irma Salvia Nisrina5 (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The integrity of legal apparatus is the main foundation in creating a fair and trustworthy justice system. This article discusses the importance of professional ethics in public service, especially for legal apparatus such as judges, prosecutors, police, and advocates. Using qualitative research methods through literature studies, this article analyzes the challenges and solutions in maintaining the integrity of legal apparatus. The results of the study indicate that strengthening the code of ethics, strict supervision, and continuing education are key to preventing abuse of authority and corruption. This article also emphasizes the need for transparency and accountability in every legal process to ensure public trust in the justice system.